Parenting Style Influencing Emotions and Attitudes Among Gifted and Talented Students - Effa Rinny Octavia Paidin; Abu Yazid Abu Bakar; Kadek Suranata (Department of Guidance and Counseling, FIP, Undiksha, 2021)
The development of emotional intelligence is formed as a result of various aspects and one of them is through social interaction among the family. This study aims to see the trend or parenting style that can influence attitudes and emotions among clever students. The focus of this study is to identify the emotional problems and attitudes of clever students, as well as to identify parenting styles that affect the emotions and attitudes of clever students. This study was carried out following the hypothesis that there was no correlation between the emotional problems of the clever students and parenting style, and there is no correlation between the problems of the attitude of the clever students with the parenting style. This is a cross-sectional study, using a non-standard questionnaire built by the researcher, which researchers obtained information on parenting styles that influenced emotions and attitudes among clever students in three high-performance schools in Kuching, Sarawak. The population of the study involved 60 students of various levels from three outstanding academic achievers in Kuching, Sarawak, randomly selected. The implications from this study, parents will be able to see and explore every one of the parenting styles that will affect the emotions and attitudes of children, thus improving themselves in giving the best love for children.